THE ROLE OF FORENSIC RADIOLOGY IN IDENTIFYING GUNSHOT WOUND - Ayu Susiyanthi; Ida Bagus Putu Alit (Universitas Udayana, 2013)
Violence cases on the rise in the community each year. This is because changes of morality consequences change attitudes and behavior. Violence can affect physical and psychological factors. Most of the persecution causes injuries; one injury that is now prevalent in our society is the result of a gunshot wound. Injuries caused by firearm to be one very dangerous injury and can lead to various types of wounds such as gunshot entrance wound, exit gunshot wounds, burns and abrasions. Radiological examination is an examination that is important enough to rate a gunshot wound primarily for ease in knowing the location of the bullet in the body of the victim and the bullet particles remained. Currently, radiologists have an important role in the field of forensic pathology and forensic medicine